Aspek Nonfarmakologis Pengobatan Albendazol Pada Cacingan: Review Sistematis - Meivie Jeanne Tumiwa; Grace Debbie Kandou; Billy Johnson Kepel (Indonesian Journal of Public Health and Community Medicine, 2021)
Background: Treatment efforts with albendazole have been implemented for a long time but intestinal worms are still a problem in Indonesia and even in the world, there are aspects or non-pharmacological factors that affect the treatment of intestinal worms with albendazole. The purpose of this study was to determine the nonpharmacological aspects of albendazole treatment in intestinal worms. Method: This research is a systematic review. Sources of research articles were taken from the PubMed database, Science direct, Wiley online library and Google scholar, with the keywords "worms" or "helminthiases" or "soil transmitted helminthes" and "albendazole" or "albendazole" and "drug adherence" or " drug complianceâ€ and â€œnutritionâ€ or â€œnutritionalâ€ and â€œageâ€ or â€œageâ€ and â€œgenderâ€ or â€œsexâ€ and â€œenvironmentâ€ or â€œsanitationâ€. A total of 6,322 articles were obtained from the initial search and from all these articles, 4 articles were found that met the criteria for analysis. The literature search was carried out in February-March 2021. The article selection process was in accordance with the guidelines from the Preferred Reporting Item for Systematic Reviews and Meta-Analysis (PRISMA). Results: A total of 6,322 articles were obtained from an electronic search by searching the PubMed database, Wiley on library and Science Direct as many as 592 articles and 5730 articles found through additional searches from Google Scholar. After screening by title, abstract and fulltext, 4 articles were found that were carried out in Asia (1 study) and in Africa (3 studies). The non-pharmacological aspects found were one study for drinking adherence factors, 1 study on nutritional factors, age and sex factors simultaneously and 2 articles related to environmental factors. Conclusion: This study conclude that four non-pharmacological aspects that affect the medication of albendazole in intestinal worms. There are medication adherence, nutrition, age and gender, and environmental factors. Therefore, it is necessary to conduct further research to see the relationship between compliance, nutrition, age, gender and environmental factors.